CORRELATION AND PATH COEFFICIENT ANALYSIS OF ECONOMICALLY IMPORTANT TRAITS IN LENTIL (LENS CULINARIS MEDIK.) GERMPLASM - VIJAY SHARMA; SUNIL KUMAR PASWAN; VIVEK KUMAR SINGH (The Bioscan, 2014)
An investigation was carried out with 80 lentil genotypes with 3 checks in augmented block design, to study correlation among the agronomical yield components and, their direct and indirect effect on seed yield. Correlation studies showed that seed yield per plant showed highly significant and positive correlation with harvest index (0.945), number of pods per plant (0.876), plant height (0.730), number of secondary branches per plant (0.576) and biological yield per plant (0.4930). Significantly inter correlation among traits is useful for breeding programme to improvement of yield and its components. Path analysis identified biological yield per plant (0.638) followed by number of pods per plant (0.286) and harvest index (0.198) as highly desirable components for direct effects on seed yield. The inter-relationship among the characters identified above used in the breeding programme to exploit the yield potential and to develop high yielding improved varieties with ease and target oriented research.